Epidemiologic characteristics of infectious disease-related public health emergencies in Guangdong province, 2014 – 2023: a surveillance data analysis - Weiyi CHEN; Runing GUO; Yun HUANG; Jianhua HUANG; Meiling YANG; Jiya DAI; Fengxiang SHI; Wenjia LIANG (Zhongguo gonggong weisheng)
ObjectiveTo analyze the epidemiological characteristics of infectious disease-related public health emergencies in Guangdong Province from 2014 to 2023, for the development of effective infectious disease prevention and control strategies and rational allocation of health resources. MethodsData on infectious disease public health emergencies reported in Guangdong province from 2014 to 2023 were obtained from the Public Health Emergency Management Information System of the Chinese Center for Disease Control and Prevention. Descriptive data analysis was performed using WPS 2019 and R 4.0.3. ResultsExcluding COVID-19 outbreaks, a total of 3 783 infectious disease-related public health emergencies were reported in Guangdong province from 2014 to 2023, of which 2 369 (62.62%) occurred in schools. The top five infectious diseases causing these public health emergencies were influenza (accounting for 18.82% of all reported emergencies), other infectious diarrheal diseases (17.42%), dengue fever (17.23%), varicella (17.00%), and hand, foot, and mouth disease (6.93%). The highest proportion of events (61.80%) were reported in the Pearl River Delta region. Among the events reported in the the Eastern Wing region, 66.09% were caused by vector-borne and zoonotic diseases and the proportion was significantly different from those in other regions. Among the four major categories of infectious diseases causing these events, vector-borne and zoonotic diseases had the highest proportion (33.10%). ConclusionsThere were regional differences in the epidemiological characteristics of infectious disease-related public health emergencies in Guangdong Province from 2014 to 2023, suggesting that region- and disease-specific measures should be developed for the prevention and control of infectious disease-related public health emergencies in the province.